Marketisation, Ethics and Healthcare Policy, Practice and Moral Formation - Feiler, Therese; Hordern, Joshua; Papanikitas, Andrew (Routledge Key Themes in Health and Society, 2018)
How does the market affect and redefine healthcare? The marketisation of Western healthcare systems has now proceeded well into its fourth decade. But the nature and meaning of the phenomenon has become increasingly opaque amidst changing discourses, policies and institutional structures. Moreover, ethics has become focussed on dealing with individual, clinical decisions and neglectful of the political economy which shapes healthcare. This interdisciplinary volume approaches marketisation by exploring the debates underlying the contemporary situation and by introducing reconstructive and reparative discourses. The first part explores contrary interpretations of 'marketisation' on a systemic level, with a view to organisational-ethical formation and the role of healthcare ethics. The second part presents the marketisation of healthcare at the level of policy-making, discusses the ethical ramifications of specific marketisation measures and considers the possibility of reconciling market forces with a covenantal understanding of healthcare. The final part examines healthcare workers' and ethicists' personal moral standing in a marketised healthcare system, with a view to preserving and enriching virtue, empathy and compassion. Chapter 4 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138735736_oachapter4.pdf Chapter 7 of this book is freely available as a downloadable Open Access PDF under a Creative Commons Attribution-Non Commercial-No Derivatives 3.0 license. https://s3-us-west-2.amazonaws.com/tandfbis/rt-files/docs/Open+Access+Chapters/9781138735736_oachapter7.pdf